Resveratrol decreases the insoluble Aβ1–42 level in hippocampus and protects the integrity of the blood–brain barrier in AD rats. (3rd December 2015) - Zhao, H.F.; Li, N.; Wang, Q.; Cheng, X.J.; Li, X.M.; Liu, T.T.
Highlights: Resveratrol decreases the insoluble Aβ1–42 level in the hippocampus in AD rats. Resveratrol protects the integrity of the blood–brain barrier in AD rats. This study can provide laboratory evidence for the prevention of resveratrol on AD rats. Abstract: Our previous studies demonstrated resveratrol (Res) administration protected Alzheimer's disease (AD) rats from developing memory decline by anti-oxidation. Beta-amyloid peptide 1–42 (Aβ1–42) is not only the primary protein component of senile plaques in AD but also is believed to play an important part in its pathology. Increasing evidence has shown neuroinflammation and the integrity of the blood–brain barrier (BBB) is closely related to the pathogenesis of AD. The aim of the present study is to further elucidate whether Res prevents AD rats from inflammation induced by Aβ1–42 and protects the integrity of BBB. Rats were divided into six groups: (1) ovariectomized (OVX) + d -galactose (d -gal) 100 mg/kg group (OVX + d -gal); (2–4) OVX, d -gal and Res 20, 40 and 80 mg/kg treated groups; and (5) OVX, d -gal and estradiol valerate 0.8 mg/kg treated group (ET); (6) Sham control group. 12 weeks later, Res 40 and 80 mg/kg treatment exhibited a significant decrease of Aβ1–42 compared with the OVX + d -gal rats of hippocampus, which was accompanied by decreased expression of advanced glycation endproducts (RAGE), matrix metalloprotein-9 (MMP-9), nuclear factor kappaB (NF-κB) and the increase of Claudin-5. These results suggest that Res is useful not only in protecting OVX + d -gal rats from neuroinflammation mediated by Aβ1–42 by decreasing the expression of NF-κB but also the integrity of BBB by increasing Claudin-5 and decreasing RAGE, MMP-9.